Pengaruh Model Pembelajaran MURDER terhadap Kemampuan Pemahaman Konsep Matematis Siswa - Fitria, Atsari; Rahmat, Tasnim; M. Imamuddin; Risnawita (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The problem in this study is the low ability to understand mathematical concepts in students. Furthermore, the learning process carried out by teachers uses conventional learning, resulting in a lack of student activeness during the learning process. This study aims to determine whether there is an effect of the MURDER learning model on students' understanding of mathematical concepts. This type of research is quantitative. The research method used is an experimental research method with a Posttest Only Group Design. The research population is grade X Phase E students at SMA N 1 Lembah Melintang. Sampling was carried out using a simple random sampling technique. The sample in this study was students from class XE2 as the experimental class, totaling 33 people, and class XE4 as the control class, totaling 33 people. The research instrument used was a test of students' mathematical concept understanding abilities. The data analysis technique using the t-test obtained t_hitung=5,08 and t_tabel=1,67. While using Minitab Software obtained P_Value=0,000. Because t_hitung>t_tabel and P_Value<α with a significance level of α=0,05, H_0 is rejected. The results of the study are